2007
DOI: 10.1002/uog.4081
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of the presence of amniotic fluid ‘sludge’ in asymptomatic patients at high risk for spontaneous preterm delivery

Abstract: K E Y W O R D S:amniotic fluid 'sludge'; chorioamnionitis; funisitis; microbial invasion of the amniotic cavity; preterm labor; preterm premature rupture of membranes; short cervix; spontaneous preterm delivery; transvaginal ultrasound ABSTRACT Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
87
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(100 citation statements)
references
References 31 publications
7
87
0
6
Order By: Relevance
“…In the present study, we found that less than 37 weeks of gestation increased the risk of PROM (OR: 4.86, 95% CI: 2.07-11.44), which was consistent with previously reported results [1,2] . The polymorphisms in some MMPs, including MMP-1 T3447C and MMP-9 C1562T, are related to PPROM [15][16][17][18] .…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, we found that less than 37 weeks of gestation increased the risk of PROM (OR: 4.86, 95% CI: 2.07-11.44), which was consistent with previously reported results [1,2] . The polymorphisms in some MMPs, including MMP-1 T3447C and MMP-9 C1562T, are related to PPROM [15][16][17][18] .…”
Section: Discussionsupporting
confidence: 82%
“…The combination of sludge and a CL <25 mm results in a higher risk for sPTB delivery at <28 and 32 weeks, than that of a short cervix alone. There is no sufficient evidence that intra-amniotic sludge alone can better the prediction accuracy already provided by CL [23].…”
Section: Technical and Clinical Aspects Of Transvaginal Cervical Sonogrmentioning
confidence: 96%
“…TVU can also help in recognizing other ultrasound risk indications for preterm delivery, including intra-amniotic sludge and choriodecidual separation [23,24]. Ultrasonography shows intra-amniotic sludge as suspended hyperechogenic material near the uterine cervix in the amniotic fluid.…”
Section: Technical and Clinical Aspects Of Transvaginal Cervical Sonogrmentioning
confidence: 99%
“…This particles could represent germs surrounded by biofilms that would hinder neutralization of germs by the antibiotics [5][6]. AF "Sludge" should not be confused with dense aggregates of fetal vermis found sometimes in normal pregnancies which disintegrates after gentle pressure with the transvaginal probe.…”
Section: Discussionmentioning
confidence: 99%